2015
DOI: 10.1111/bcp.12642
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after TNF‐α inhibitor therapy during the first trimester: a prospective multicentre cohort study

Abstract: Aims TNF‐α inhibitors are considered relatively safe in pregnancy but experience is still limited. The aim of this study was to evaluate the risk of major birth defects, spontaneous abortion, preterm birth and reduced birth weight after first trimester exposure to TNF‐α inhibitors. Methods Pregnancy outcomes of women on adalimumab, infliximab, etanercept, certolizumab pegol or golimumab were evaluated in a prospective observational cohort study and compared with outcomes of a non‐exposed random sample. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 48 publications
4
78
0
7
Order By: Relevance
“…These results are not easy to interpret since no distinct pattern of malformations could be identified which would be expected for typical teratogens. In addition, the rate of 1.5% major birth defects in the comparison cohort is lower than the prevalence of all non-chromosomal anomalies of 2.2% recorded by EUROCAT [97]. TNF inhibitors that contain an Fc part of an IgG molecule are actively transported from the maternal to the fetal circulation starting at around week 18 of gestation [98].…”
Section: Tnf Inhibitors and Pregnancymentioning
confidence: 77%
“…These results are not easy to interpret since no distinct pattern of malformations could be identified which would be expected for typical teratogens. In addition, the rate of 1.5% major birth defects in the comparison cohort is lower than the prevalence of all non-chromosomal anomalies of 2.2% recorded by EUROCAT [97]. TNF inhibitors that contain an Fc part of an IgG molecule are actively transported from the maternal to the fetal circulation starting at around week 18 of gestation [98].…”
Section: Tnf Inhibitors and Pregnancymentioning
confidence: 77%
“…The risk of miscarriage was not increased in the exposed cohort (9.3 vs. 7.9%). The authors concluded that the use of TNF-α inhibitors during pregnancy may carry a risk of adverse pregnancy outcomes of moderate clinical relevance (major birth defects and preterm birth: adalimumab [6%, 17.4%]; infliximab [4.5%, 16%]; etanercept [5.4%, 17.9%], respectively) [24]. In contrast, in the current study, no fetal or neonatal congenital abnormalities and 4 (8.2%) miscarriages were observed in 49 pregnancies exposed to adalimumab during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…defects, preterm birth, and low birth weights than control, 19 however, most of the women in this study were on TNF-α inhibitors for inflammatory bowel disease or rheumatoid arthritis, which can independently result in preterm birth and low birth weights. Psoriasis and psoriatic arthritis patients accounted for only 8% of the pregnancies in this study, making it unclear whether the poorer fetal outcomes in the exposed group were a result of the underlying severe disease or of TNF-α inhibitors exposure.…”
Section: Psoriasismentioning
confidence: 59%
“…5, 16, 17 TNF-α biologics cannot cross the placenta until after 20 weeks" gestation, when most organogenesis is complete. 17,19 A recent prospective cohort study found that women exposed to TNF-α inhibitors during pregnancy had a higher risk of birth…”
Section: Psoriasismentioning
confidence: 99%